Are public health measures and individualised care compatible in the face of a pandemic? A national observational study of bereaved relatives' experiences during the COVID-19 pandemic. (September 2021) - Mayland, Catriona R; Hughes, Rosemary; Lane, Steven; McGlinchey, Tamsin; Donnellan, Warren; Bennett, Kate; Hanna, Jeffrey; Rapa, Elizabeth; Dalton, Louise; Mason, Stephen R
Background: COVID-19 public health restrictions have affected end-of-life care experiences for dying patients and their families. Aim: To explore bereaved relatives' experiences of quality of care and family support provided during the last days of life; to identify the impact of factors associated with perceived support. Design: A national, observational, open online survey was developed and disseminated via social media, public fora and professional networks (June–September 2020). Validated instruments and purposively designed questions assessed experiences. Analysis used descriptive statistics, logistic regression and thematic analysis of free-text responses. Participants: Individuals (⩾18 years) who had experienced the death of a relative/friend (all care settings) within the United Kingdome during the COVID-19 pandemic. Results: Respondents ( n  = 278, mean 53.4 years) tended to be female ( n  = 216, 78%); over half were 'son/daughter' (174, 62.6%) to the deceased. Deceased individuals (mean 81.6 years) most frequently died in their 'usual place of care' ( n  = 192, 69.3%). Analysis established five conceptual themes affecting individualised care: (1) public health restrictions compounding the distress of 'not knowing'; (2) disparate views about support from doctors and nurses; (3) challenges in communication and level of preparedness for the death; (4) delivery of compassionate care; (5) emotional needs and potential impact on grief. Male respondents (OR 2.9, p  = 0.03) and those able to visit (OR 2.2, p  = 0.04) were independently associated with good perceptions of family support. Conclusion: Despite public health restrictions, individualised care can be enabled by proactive, informative communication; recognising dying in a timely manner and facilitating the ability to be present before death.